Efektivitas Sistem Pengendalian Internal Piutang Anggota Pada Koperasi Kredit Swasti Sari Kupang - Leu, Theresia Fouk; Widyasari, Yolanda O. M. (CV. ITTC INDONESIA, 2022)
The problem studied in this study is the weakness of the internal control system, such as there are still cooperative members who are late in paying their installments and there are also task traps. The formulation of the problem in this study is how the Level of Effectiveness of the Internal Control System of Member Receivables in the Swasti Sari Kupang Credit Cooperative. The purpose of this study is to determine the effectiveness of the internal control system of member receivables at the Swasti Sari Kupang Credit Cooperative. In accordance with the results of data analysis that has been stated in the previous chapter, it can be concluded that the internal control system of member receivables seen from 4 (four) research indicators, namely organizational structure, The authority system and recording procedures, healthy practices and competent employees at the Swasti Sari Kupang Credit Cooperative are classified as Effective, in accordance with the results of the calculation of the percentage of respondents' answers who answered Yes by 86.22%, which means that the Swasti Sari Kupang Cooperative has implemented elements of the implementation of the Member Receivables SPI, namely, the existence of an Organizational Structure, Authority System and Recording Procedures, Healthy Practices and Competent Employees. The advice given based on the results of this study is: For the Swasti Sari Kupang Credit Cooperative, namely to maintain the Effectiveness of the Internal Control System that has been implemented so far. And it is also expected that institutions pay attention to the weaknesses of the internal control system such as: occurring task traps, there are members of the Cooperative who are late in paying their installments. For other research, this thesis can be used as a reference for other research in conducting similar research or further research on the Effectiveness of the Internal Control System for Member Receivables.